Estudo da influência das resinas termofixas uréia formaldeído (UF) e melamina formaldeído (MF) nas características físicas e mecânicas de painéis MDF - Silva, José Eduardo Estevam da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Thermosetting resins are very important in the production of MDF panels. They act as an adhesive in the process of compacting and consolidating the fiberboard. Thermoset resins commonly used in this process are based resin urea formaldehyde (UF) and melamine formaldehyde (MF). The first has a higher demand due to its low cost and good performance in meeting the specifications and standards. The second has a high cost compared to MF resin, but adds greater value to the MDF panel, because it gives greater moisture resistance. The process of manufacture of MDF boards was briefly presented in this study to facilitate the understanding of the work. Samples of thermosetting resins (UF and MF) were subjected to physical-chemical seeking to relate these results to the technological performance presented by their respective samples of MDF boards. Two other samples of MDF panels were subjected to physical and mechanical tests. Results were analyzed and related to the award of their respective thermoset resin. Instruments like Dahmos Trend Manager ® and Grecon Dax 5000 and TG - DSC analysis were used in this study to assist in the analysis of the results. It was observed that the results of the analysis of thermosetting resins were within the specified. Such resins do not directly influence the technological tests provided by the MDF panels, but it has been found that the process variables such as humidity and fiber production rate interfere with the performance of the resin accelerating the reaction and therefore their influence on the physical-mechanical properties of the panels MDF. Samples of MDF panels with UF and MF met all the specifications required by the Brazilian standard with regard to the technological quality. The increased demand for UF resin market is justified by the service specifications...
Keywords: Indústria de móveis; Testes quimicos e reagentes; Chapa de madeira aglomerada; Quimica; Furniture industry and trade